ANALISIS EFEKTIVITAS UPTD BALAI LATIHAN KERJA (BLK) DISNAKER KOTA SEMARANG DALAM MENINGKATKAN KETERAMPILAN MASYARKAT KOTA SEMARANG - M.Fajar Asshiddiq Simatupang; Purwoko .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2017)
Poverty happens in many areas in Indonesia is a classic problem, as poverty will trigger a crime or criminality,because indeed human resource needs to survive hence the need for training and the coaching job for the community.Work Practice UNIT BLK formed Government in effort to overcome poverty and unemployment in the Semarang City with infrastructures and training places to get skills or who want to deepen their expertise in their fields . This research is a policy studies analyzing the effectiveness of UNIT BLK and efforts made Semarang Government in running the training program with qualitative descriptive methods. This research was conducted in Semarang City, Central Java. With the techniques of data collection through interview and documents.In the implementation of a training program in UNIT BLK Disnaker Semarang city researchers found factors that affect success rate of good facility or infrastructure in the process including job training efforts that have been undertaken by Governments. As well as the researchers found effectivity variables of an organization that has not been fulfilled and affect the effectiveness of an organization. Especially in these research, findings one is the lack of permanent trainers and training material that have not been in accordance with the times, which need the ability and expertise to continue to increase. Recommendations of researchers need to immediately recruit instructors remain and have been officially training as well as the need to enhance cooperation with private parties both companies and so on, in order to improve the learning material that suit the market needs, as well as the training of graduates who have made the standards of good competence. Keywords: poverty, effectiveness, Organization, policies